Deintegration in the European Union and lessons for Asia - Golam Robbani (Asian Development Bank Institute (ADBI), 2020)
The European Union (EU) is one of the most successful integration arrangements in the world. However, the disintegration in Europe through Brexit is puzzling. This article aims to clarify this dilemma by addressing the following questions: Was the former French President, de Gaulle, right that the United Kingdom (UK) did not fit in the EU? Is it that the UK government failed to redistribute the gains from EU membership equitably to the Britons who voted for Brexit? Is Brexit happening due to a deceptive campaign? Or was it just the sovereignty that Britons do not want to sacrifice no matter what economic costs they face? This paper aims to clarify why Brexit happened and what lessons can be learned from Brexit for other integration arrangements around the world - especially in Asia. This paper argues that Brexit reminds us of the limitations of regional integration. It strongly advises policy makers to be cautious in expanding too far and too fast and suggests paying proper attention to educating citizens about the costs and benefits of regional integration.
Keywords: F15; F1; D31; R5; 330; Brexit; European Union; economic integration; Asia